Лекарственные средства: пособие по фармакотерапии для врачей: в 2-х частях (М. Д. Машковский) - Машковский Михаил Давыдович (1988)
Экземпляры: ЧЗ (20180926) / Инвентарный номер: 23003 / Цена: 3.50 / Сис.шифр: 52 / Авт.знак: М 38 / ГРНТИ: 76 / ББК: 52.8